KRIPTOGRAFI FILE CITRA MENGGUNAKAN ALGORITMA TEA (TINY ENCRYPTION ALGORITHM) - Mukti Qamal (Teknik Informatika Universitas Malikussaleh, 2014)
The sharp growth of data communication recently raise the importance of data security and confidentiality. Cryptography is the art or science of maintaining the security of data or message that randomize the data or message. In addition to text-based documents, it is also common to send image through a network. This research investigates the way to secure the image from the cryptanalyst disorders by using TEA (Tiny Encryption Algorithm) algorith, which is a secret key cryptographic algorithm. The strength of this algorithm lies in the Feistel network and the number of delta derived from the golden number. It was found that the algorithm is appropriate for encrypting and decrypting image, because of stronger round quantity and key length, and does not need S-box and P-box in the process. The test showed that this algorithm with 32 round fits highly for securing images with optimum speed. It was also found that the bigger image size, the longer the encryption and decryption process takes time to run, with decrypted image has different bit depth value compared to original image.